2010
DOI: 10.1111/j.1538-7836.2010.03945.x
|View full text |Cite
|
Sign up to set email alerts
|

Definition and drivers of acute traumatic coagulopathy: clinical and experimental investigations

Abstract: Summary. Background: Acute traumatic coagulopathy (ATC) is an impairment of hemostasis that occurs early after injury and is associated with a 4-fold higher mortality, increased transfusion requirements and organ failure. Objectives: The purpose of the present study was to develop a clinically relevant definition of ATC and understand the etiology of this endogenous coagulopathy. Patients/methods: We conducted a retrospective cohort study of trauma patients admitted to five international trauma centers and cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
292
3
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(311 citation statements)
references
References 29 publications
9
292
3
7
Order By: Relevance
“…Fung et al [15] also evaluated nontraumatic hemorrhage without impairing coagulation in an ovine model. Some reports have shown that hemorrhagic shock may play an integral role in the progression of early coagulopathy, [16,17] but our results revealed that hypoperfusion, lower temperature and acidosis may exacerbate the development of coagulopathy. Coagulation dysfunction was not initiated by the isolated hemorrhagic shock.…”
Section: Discussioncontrasting
confidence: 47%
“…Fung et al [15] also evaluated nontraumatic hemorrhage without impairing coagulation in an ovine model. Some reports have shown that hemorrhagic shock may play an integral role in the progression of early coagulopathy, [16,17] but our results revealed that hypoperfusion, lower temperature and acidosis may exacerbate the development of coagulopathy. Coagulation dysfunction was not initiated by the isolated hemorrhagic shock.…”
Section: Discussioncontrasting
confidence: 47%
“…Hypoperfusion plays a critical role in the pathogenesis of ATC as demonstrated in numerous clinical studies [3,6,[42][43][44][45][46][47][48][49][50][51], animal models [6,50] and in vitro experiments [22,51]. These data indicate that as shock severity increases, the PT and INR rise [4,5,7,52] and coagulation factor levels fall [6,48]. The most compelling of these studies, that included 3646 patients, demonstrated that ATC (INR > 1.2) occurred only when significant hypoperfusion (base deficit > 6 mmol.l…”
Section: Pathophysiologymentioning
confidence: 84%
“…This is mainly due to the recognition that many patients who are bleeding when they come to the emergency department have an established coagulopathy before the dilutional effects of fluid resuscitation. Traumatic coagulopathy has been demonstrated in patients who received little or no intravenous fluid therapy, negating the long-held belief that iatrogenic haemodilution is the main causative factor in traumatic coagulopathy [3][4][5][6]. This has led to the use of new terminology: acute traumatic coagulopathy (ATC); acute coagulopathy of trauma shock or traumainduced coagulopathy.…”
Section: Introductionmentioning
confidence: 99%
“…A multicenter retrospective study of over 3646 trauma patients confirmed that the severity of TIC is strongly associated with combined severe injury and shock. 32 A synergistic effect of materials released from tissue injury with inflammation and anticoagulant factors induced by endothelial injury and tissue hypoxia likely mediate this relationship to produce TIC.…”
Section: Combining Injury and Shock To Produce Ticmentioning
confidence: 99%